DETERMINATION OF THE SEISMIC STRENGTH OF AN OIL PRODUCT STORAGE TANK IN THE PRODUCT-FILLED CONDITION (Eureka Journal of Civil, Architecture and Urban Studies, 2025)
This article develops technical solutions aimed at reducing the seismic hazard identified in existing storage tanks. Scientific and technical proposals focused on increasing the seismic resistance of the tank are formulated, and constructive strengthening measures are developed based on the results of calculations performed using the LIRA-SOFT 10.12 software package. Based on the obtained results, effective technical solutions are proposed to mitigate seismic effects and enhance the overall safety of the tank.
Keywords: LIRA-SOFT 10.12 software, seismic loads, equivalent stress, stiffening ribs, loads, stiffness parameters, dynamic effects.